The interaction between constituent year and within-1-year effects in elite German youth basketball - Steingröver, C.; Wattie, N.; Baker, J.; Helsen, W. F.; Schorer, J. (Scandinavian Journal of Medicine & Science in Sports, 2017)
The current state of research on relative age effects in basketball shows an uneven picture. These mixed results might be caused by the interaction of constituent year and within-year effects. Our aim was to examine constituent and within-1-year effects in elite German youth basketball. The sample (n = 4400) included players competing in the JBBL (Under-16 first division) and the NBBL (Under-19 first division) from 2011/2012 until 2013/2014. A multi-way frequency analysis revealed an interaction of constituent year effects and within-1-year effects for the JBBL, X2(6, 2590) = 12.76, P < 0.05. NBBL data showed significant constituent year effects, X2(2, n = 1810) = 25.32, P < 0.01, and within-1-year effects for all three age bands but no interaction. The interaction between constituent year and within-1-year effects in the JBBL showed reduced within-1-year effects with increasing age. Once players enter the system in the JBBL, relatively younger players seem less likely to drop out of the system. Results offer new insight regarding how the regulations of this talent development system may influence athletes' opportunities to enter the system and their likelihood of staying at the highest levels of competition.